Models of Improving The Quality of Education From The Perspective of Education Management - Tamlekha Tamlekha; Sunan Hanif Ihsan Assalaam; Uus Ruswandi (Jurnal Ilmiah Teunuleh, 2026)
Quality of education is one of the main indicators of the success of education implementation and has a strategic role in human resource development. The low quality of graduates, weak relevance of education to the needs of the community, and lack of effective management of educational institutions show that quality improvement cannot be separated from education management. This article aims to examine the concept of education quality, describe various models for improving the quality of education, and analyze these models from the perspective of education management. This study used a qualitative approach with a literature review method. Data were obtained from national and international journal articles, proceedings, research reports, and other relevant academic documents. Data were analyzed using content analysis techniques through conceptual grouping, model categorization, and theory synthesis. The results of the study show that quality of education is the result of a planned and sustainable management process, which includes the dimensions of input, process, output, and outcome. Various models of education quality improvement, such as total quality management, school-based management, continuous improvement, the input-process-output model, and internal quality assurance, have a strong theoretical and relevant foundation to be applied in education management. The perspective of education management helps us understand that quality improvement requires a systemic approach, effective leadership, supportive organizational culture, and the participation of all stakeholders.